New approach of Lebesgue integral in revised fuzzy cone metric spaces via unique coupled fixed point theorems - Thangathamizh, Ravichandhiran; Muraliraj, Angamuthu; Shanmugavel, Periyasamy (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: This article introduces the concept of revised fuzzy cone contraction by using the concept of a traiangular conorm and Revised Fuzzy Cone contractive conditions. Methods: This article established new Revised Fuzzy Cone Contraction (RFC-C) type unique coupled Fixed Point theorems (FP theorems) in revised fuzzy cone metric spaces (RFCMS) by using the triangular property of RFCMS.Results: The obtained results on fixed points in revised fuzzy cone metric spaces generalize some known results in the litrature and present illustrative examples to support the main work.Conclusion: The RFC contractive conditions generalize some important contraction types and examine the existence of a fixed point in revised fuzzy cone metric spaces. In addition, the Lebesgue integral type mapping is applied to get the existence result of a unique coupled fixed point in RFCMS to validate the main work.
Keywords: revised fuzzy metric; revised fuzzy cone; fixed point